Tiny thoughts on sharing - Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
beauty Bear is a little greedy and wants more for herself but then experiences the wonderful feeling of being unselfish and sharing
Education
For children from 3 to 6 years old
1
Keywords: Educational psychology